Comprehension priming in Chinese EFL learners’ reflexive pronoun interpretation - Yang, Lianrui; Song, Zimiao; Wei, Yinxia (Frontiers in Psychology, 2024)
Reflexive interpretation is a pivotal aspect of discourse comprehension, which usually reveals consistent challenges for Chinese EFL learners. These learners often breach the locality constraint of reflexive pronouns, exhibiting a persistent tendency towards optional reflexive comprehension. Recent research has demonstrated the effectiveness of the priming technique in altering biases among L2 learners in anaphora resolution. However, no existing studies have investigated comprehension priming in the context of reflexive interpretation among Chinese EFL learners. This study addresses this gap by conducting a sentence comprehension experiment with 36 high school students to explore the potential of comprehension priming in modifying L2 learners’ reflexive interpretation biases and examining the persistence of the priming effect. The findings reveal immediate and cumulative priming effects, with no discernible effect observed after 1 week. The results suggest that comprehension priming can occur universally, even without lexical overlap, previously assumed to be a prerequisite. While the priming effect lacks statistical significance after 1 week, there is a numerical increase in participants consistently interpreting the target structure correctly. Thus, comprehension priming emerges as an effective method for L2 learners to internalize more abstract linguistic rules. Further research on comprehension priming across diverse L2 populations and language structures is warranted.